Elaboration of a piezoelectric force sensor for medical application. Issue 1 (November 2021) - Chelli, Zakia; Achour, Hakim; Saidi, Malika; Laghrouche, Mourad; Ahcene, Chaouchi
Abstract: In this work, a piezoelectric force sensor was fabricated based on Lead-Free ferroelectric particles (Na0.535 K0.48 )0.966 Li0.058 Nb0.9 Ta0.1 O3 (NKLNT) synthesized by solid-state route. A piezoelectric characterization by FTIR spectroscopy and dielectric characterization was performed. The manufactured NKLNT sensor shows excellent sensitivity and response to external mechanical forces, which implies that this sensor presents a promising technology for different applications.